89603892387 Kedudukan Amicus Curiae Dalam Hukum Acara Pidana Di Indonesia (Studi Putusan Pengadilan Negeri Nomor 798/Pid.B/2022/PN Jkt.Sel) - Pratiani, Olivia; Kartika, Adhitya Widya (PERSPEKTIF : Kajian Masalah Hukum dan Pembangunan, 2024)
The purpose of this research is to determine the position of this foreign concept in the Indonesian legal system, specifically criminal procedural law, and to examine the existence of the amicus curiae concept in the settlement of case number 798/Pid.B/2022/PN Jkt.Sel while linking its existence in the case with the principle of res judicata pro veritate habetur, which is inherent in every decision product of an institution with the authority to adjudicate. This research was conducted in a normative juridical manner using literature or secondary data and an analytical method in the form of in-depth analysis that produces sentences according to the rules or is called qualitative. The selection of this title focuses on the position of amicus curiae itself in Indonesian criminal justice and its role in the judge’s legal considerations that result in a decision in a particular case. More or less it was found that the position of this concept is not explicitly regulated in any regulations in Indonesia, but its existence can still be found because in fact there are several regulations that indicate this concept can be used. The existence of this concept in the settlement of cases resulting in court decisions remains within the principle of res judicata pro veritate habetur, which means that it is not appropriate to doubt the decision even though it is known that there is a contribution from amicus curiae who do not have a clear position.